A Study on Students’ Ability in Understanding Gender of Noun at The Tenth Grade SMAS Kurnia Jaya Rupat - Supriatin Supriatin; Ade Silvana (STAIN Bengkalis, 2021)
Many students cannot differentiate nouns in gender. The purpose of the research is to find out students’ ability in understanding the gender of nouns. The research has been conducted from May up to July 2019. This research was Tenth Grade SMAS Kurnia Jaya Rupat and the object was the students’ ability to understand the gender of the noun. The number of students was 68 students, 34 students as a sample that using purposive sampling. The researcher used the descriptive quantitative method. It can be concluded that the percentage of the students’ ability to understand the gender of nouns at Tenth Grade of SMAS Kurnia Jaya Rupat was “fair”. Where the mean score of students’ ability in understanding masculine gender was “fair”, the mean score of students’ ability in understanding feminine gender was “fairly good”, the mean score of students’ ability in understanding common gender was “fair” and the mean score of students’ ability in understanding neuter gender was “fairly good”. Based on the mean score for each part, it can be seen that the part gender of the noun was difficult in common gender with the mean score “fair” and the part gender of the noun was the easiest in neuter gender was “fairly good”.